Histories, practices, interventions: a reader in Singapore contemporary art - Say, Jeffrey (Institute of Contemporary Arts Singapore, 2016)
"This publication is the first to provide a compilation of writings on contemporary art and artists in Singapore. It features 33 texts by diverse hands, culled from a variety of sites and spanning the 1970s through the first 10 years of this century."--Foreword
Includes bibliographical references